The Effect of Job Placement and Compensation on Employee Satisfaction of PDAM Bau-Bau - Dwi Agustyawati; Wa Ode Al Zarliani; Hasni; Husna Katjinah (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2022)
This study aims to determine whether job placement and compensation affect employee satisfaction of PDAM Baubau. The data collection method used is descriptive quantitative with an analytical tool for testing against hypotheses is the t (t-Partial) test. The study was conducted on 54 respondents from 120 employees of PDAM Baubau. Based on the results of the study, it is proven that job placement has a positive and significant effect on employee satisfaction of PDAM Baubau and compensation has a positive and significant effect on employee satisfaction of PDAM Baubau